Microbiological survey of sugar gliders (Petaurus breviceps) kept as pets in Italy. (1st December 2019) - Varriale, L.; Russo, T.P.; Pace, A.; Mediatore, S.; Borrelli, L.; Santaniello, A.; Menna, L.F.; Fioretti, A.; Dipineto, L.
Abstract: The sugar glider ( Petaurus breviceps ) is a small, arboreal, nocturnal, gliding mammalian possum belonging to the marsupial infraclass. Exotic marsupials, including sugar gliders, are becoming popular companion pets and, consequently, the risk of potential infections that can be transmitted to humans should be investigated. Data on the role of the sugar glider as a possible carrier of pathogenic and zoonotic bacteria are scarce and fragmentary. Therefore, this study is aimed at evaluating the prevalence of potentially zoonotic bacteria ( Salmonella spp., Escherichia coli, Campylobacter spp., Pseudomonas spp., Klebsiella spp., Listeria monocytogenes and Yersinia enterocolitica ) in 64 sugar gliders kept as pets in Italy. The highest prevalence of infection pertained to members of the family Enterobacteriaceae, in particular Citrobacter spp. (50%), Enterobacter spp. (28·1%) and Klebsiella pneumoniae (15·6%); Pseudomonas aeruginosa was isolated from 10 out of 64 samples (15·6%). All strains of Klebsiella pneumoniae exhibited some level of resistance to multiple antimicrobials (ampicillin, amoxicillin‐clavulanic acid and doxycycline). Significance and Impact of the Study: The results of this study show that sugar gliders may act as carriers of potentially pathogenic agents for humans and other animal species, therefore caution should be exercised in the handling and contact with these animals.